The suicide triggers among atikamekw and anishnabek - Lívia Vitenti (Drogues, santé et société, 2019)
This article is devoted to the discussion about suicide’s trigger in two communities with representatives of First Nations of Quebec: the Atikamekw, from Manawan, and the Anishnabek from Lac Simon. Broadly speaking, these triggers, also known as “immediate factors”, are, beyond addictions – alcohol and drugs – depression, and violence – physical, psychological, or sexual. We also offer a discussion of the lack of affection and the residential school system, which is analyzed as having a potential link with the causes of voluntary death. Analyses will be based largely on our fieldwork in both communities from an anthropological and ethnographical approach. We primarily used methods of participant-observation and unstructured interviews with members of both communities. On the subject of suicide, we obtained different points-of-view, which have led us to understand the negative effects of these triggers, but at the same time, showed us that they do not determine the act of suicide. While this article is dedicated to suicide triggers, we stress that such triggers are part of a greater range of events. Cet article est consacré à la discussion sur les déclencheurs du suicide chez deux communautés représentant des Premières Nations du Québec, soit les Atikamekw de Manawan et les Anishnabek du Lac Simon. Ces déclencheurs, aussi appelés « facteurs immédiats », sont, grosso modo, au-delà des dépendances – alcool et drogues – la dépression et la violence – physique, psychologique et sexuelle. Il traitera aussi du manque d’affection et du système de pensionnat, qui seront analysés comme susceptibles d’avoir un lien avec les causes de la mort volontaire. L’analyse sera surtout basée sur notre expérience de recherche sur le terrain dans les deux communautés, à partir d’une approche anthropologique et ethnographique. La méthode de l’observation participante et des entrevues non structurées avec des membres de deux communautés a été principalement utilisée. Nous avons obtenu plusieurs informations sur le sujet, ce qui nous a ...